2022
DOI: 10.1136/archdischild-2022-324047
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and aetiology of infant Gram-negative bacteraemia and meningitis: systematic review and meta-analysis

Abstract: BackgroundOne in six infant deaths worldwide are caused by invasive bacterial infections, of which a substantial but unquantified proportion are caused by Gram-negative bacteria.MethodsWe conducted a systematic review of studies published from 31 May 2010 to 1 June 2020 indexed in MEDLINE, Embase and Global Health databases. We performed meta-analyses of the incidence of Gram-negative bacteraemia and of individual Gram-negative species as proportions of all infant bacteraemia, stratified by onset (early vs lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Ampicillin-resistant: Ceftriaxone 100.0 mg divided into two doses OR cefotaxime 200.0 to 300.0 mg divided into four doses PLUS gentamicin 7.5 mg divided into three doses. Length therapy, 21 days ( 131 ).…”
Section: Meningococcal Meningitismentioning
confidence: 99%
“…Ampicillin-resistant: Ceftriaxone 100.0 mg divided into two doses OR cefotaxime 200.0 to 300.0 mg divided into four doses PLUS gentamicin 7.5 mg divided into three doses. Length therapy, 21 days ( 131 ).…”
Section: Meningococcal Meningitismentioning
confidence: 99%
“… 1 , 35 , 36 , 37 A systematic review found that K pneumoniae is the leading cause of Gram-negative meningitis and bacteraemia in low-income and middle-income countries. 38 Despite its high fatal burden, K pneumoniae is not included as a priority pathogen in WHO's meningitis global roadmap, 13 possibly because of a scarcity of global data on meningitis due to K pneumonaie before this study. K pneumoniae is also not included in most commercially available PCR or rapid diagnostic tests.…”
Section: Discussionmentioning
confidence: 98%
“…Escherichia coli is one of the most well-adapted and pathogenically versatile bacterial organisms ( Riley, 2020 ). It is the main pathogen causing neonatal meningitis and sepsis especially in developing countries ( Tan, 2020 ; van der Flier, 2021 ; Wen et al., 2021 ; Hallmaier-Wacker et al., 2022 ), also a common pathogen of ventilator associated pneumonia (VAP) in hospitals( Scamardo et al., 2020 ). According to the data from the Neonatal Monitoring Network released by NICHD (the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network) in 2020 ( Stoll et al., 2020 ), the most frequent pathogens of early onset neonatal sepsis were E. coli (36.6%) and Group B streptococcus (30.2%), and E. coli mainly occurred in premature infants (51.9%).…”
Section: Introductionmentioning
confidence: 99%